Twenty years of experience running calibration baseline - Būga, Arūnas; Putrimas, Raimundas (International Conference “Environmental Engineering”, 2017)
The authors of the paper are sharing their 20 years of experience in using Kyviškės Calibration Baseline. The Kyviškės Calibration Baseline (1320 m) is the longest calibration baseline in Lithuania. The baseline is calibrated regularly with 5–7 years period. The first time these measurements were performed in 1997 and repeated in 2001, 2007, 2008 and 2014. The same Kern Mekometer ME5000 EDM (electronic distance measurement) instrument was used for all the measurements performed. By building additional pillar aside from the baseline pillars the Kyviškės Baseline was converted to a triangle-shaped test field in 2000. The results confirm good stability of the baseline, which is now used for calibration of the EDM instruments, total stations and GNSS (global navigation satellite system) receivers.
Keywords: calibration; baseline; EDM; length measurement